Penerapan Decision Making System dalam Seleksi Pemilihan Salesperson Berdasarkan Multi-Kriteria - Gusriva, Revi (Pustaka Galeri Mandiri, 2025)
The sales recruitment process in the housing industry requires objective and measurable candidate evaluation so that companies can select truly competent salespeople. However, manual selection processes often lead to subjectivity and slow decision-making. This study aims to develop a Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to select sales candidates based on multiple criteria relevant to the needs of the property industry. The criteria used include communication skills, work experience, digital marketing skills, negotiation skills, and professional appearance and ethics. The SAW method was chosen because it can perform simple, fast, and accurate weighting calculations to generate the best alternative value based on all predetermined criteria. The results show that this system can assist companies in determining sales candidates who best meet competency standards through a transparent and measurable ranking process. Thus, the application of the SAW method to the sales selection process has proven effective in supporting more objective, efficient, and aligned decision-making in the digital era. Hasil akhir penelitian ini diperoleh 4 rekomendasi sales dengan nilai akhir Perhitungan SAW menghasilkan nilai untuk setiap kandidat, dengan skor tertinggi diperoleh pada kandidat V16 dan V19 sebesar 0,898, serta diikuti kandidat V10 dengan nilai 0,731. Kandidat-kandidat dengan nilai tertinggi tersebut direkomendasikan sebagai calon sales terbaik karena memenuhi standar kompetensi yang sesuai dengan kebutuhan perusahaan